TINJAUAN KRITIS TERHADAP ISTILAH METODE CAMPURAN (MIXED METHOD) DALAM RISET SOSIAL - Aan Juhana Senjaya (Risâlah, Jurnal Pendidikan dan Studi Islam, 2018)
The study of mixed methods in research methodology has become a 'trend' or a trend back after not appearing for several periods. Emerging issues about mixed methods are usually surrounded by definitions, paradigms, and methodologies. Researchers when writing about Mixed Methods raises issues around design, sampling, analysis, and reporting that require skills, cost, and time to research with mixed methods. This paper aims to conduct a critical study of the term mixed methods (Mixed Methods) so it can be more clear what is meant by mixed methods. Hopefully, novice researchers who are interested in doing research do not "euporia" using mixed methods for any phenomenon and problem. Research is essentially answering a question or a researcher's doubt on a particular phenomenon or problem based on a scientific procedure. Thus, the approach and method of research used depend on the problem and purpose of the research itself. On the other hand, humans view the phenomenon of nature highly dependent on the way of looking at the world which later became the paradigm of his thinking about the world and its various phenomenon.